Pengaruh Persepsi Kemudahan, Keamanan, dan Pengaruh Sosial terhadap Minat Penggunaan QRIS sebagai Metode Pembayaran di Bandar Lampung - Aderia Hanifa Ananda; Nova Mardiana (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
The study try to explain the influence of perceived ease of use, perceived security, and social influence on consumer interest in adopting the QRIS as a digital payment method in Bandar Lampung. The rapid growth of digital transactions and the shift toward non-cash payments highlight the importance of understanding the factors that encourage consumer adoption of QRIS. A quantitative approach was employed, collecting primary data from 222 respondents through structured questionnaires distributed in various retail and public settings. The data were measured with Pearson correlation, and simple linear regression to measure the strength and significance of the variable’s relationships. The findings indicate that all three factors significantly influence consumer interest, with social influence showing the strongest effect, followed by perceived security and perceived ease of use. The results suggest that social norms, trust in transaction security, and ease of interaction with the system are critical in motivating consumers to adopt QRIS. These insights provide practical implications for service providers, policymakers, and merchants to enhance digital payment adoption by focusing on user-friendly designs, robust security measures, and strategies that leverage social influence to encourage broader usage.